Electrical properties and electromagnetic shielding effectiveness of polyester yarns with polypyrrole deposition - USTA, İSMAİL; YILDIZ, ZEHRA (SAGE PUBLICATIONS LTD, 2012)
Polypyrrole was deposited on polyester yarns by vapour phase polymerization technique. Ferric chloride was used as an initiator. In order to determine the effect of the initiator concentration on polymerization process, four different initiator concentrations (0.2, 0.4, 0.6 and 0.8 mol/l) were used. The effect of the initiator in terms of tensile properties, electrical resistivities and morphological properties of the yarns was investigated. The polypyrrole deposited polyester yarns were then weaved in a handloom to form fabric for the investigation of surface resistivity and electromagnetic shielding effectiveness. Scanning electron microscopy, energy dispersive spectroscopy and Fourier transform infrared analyses illustrated that polypyrrole has penetrated into the yarn structure and the highest polypyrrole deposition was obtained at the initiator concentration of 0.6 mol/l. Also, the highest electromagnetic shielding effectiveness value and the lowest surface resistivity were obtained at this concentration.
Keywords: Polypyrrole (PPy); conductive textiles; vapour phase polymerization; electromagnetic shielding; polyester (PES); VAPOR-PHASE POLYMERIZATION; ELECTROCHEMICAL POLYMERIZATION; CONDUCTIVE POLYPYRROLE; WOOL YARNS; PYRROLE; COMPOSITES; PARAMETERS; TEXTILES